Sidenreng Rappang History Museum with a Neo-Vernacular Architectural Approach - Annisa Nurfitria; Nurhayati Kamaruddin; Sultan La Obo (Universitas Ichsan Sidenreng Rappang, 2026)
The introduction of this research is motivated by the importance of artificial lighting quality in classrooms on the academic performance of architecture students. Many studies have shown that good lighting can improve concentration and material comprehension, but few studies have specifically examined its impact on architecture students in Indonesia, particularly at Ichsan University, Sidenreng Rappang. An abstract consists of 150-250 words and includes the core information of the research or work. This study aims to analyze how the quality of artificial lighting affects the academic performance of students in the architecture program. The research method used is a descriptive quantitative approach, where data were collected through surveys and measurements of lighting quality in several classrooms. Students' academic performance was measured and compared to the existing lighting conditions, using statistical analysis to determine the correlation. The results indicate a significant relationship between the quality of artificial lighting and improved student academic performance. In conclusion, improving the quality of classroom lighting can positively impact the academic performance of architecture students.